Maintaining Salafi Values through Innovative Management Practices at Pesantren - Ruchman Basori; Tri Joko Raharjo; Titi Prihatin; Arief Yulianto (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2023)
This research investigates the dynamic management strategies implemented by Tegalrejo Asrama Perguruan Islam (API) Pesantren, addressing the challenges of modernization and community demands. Utilizing a qualitative field study approach, the focus is on exploring innovative change management models in Islamic boarding schools. The findings reveal that API Tegalrejo Pesantren successfully navigates modernization challenges through innovative practices such as integrating general and religious education, conducting extracurricular programs, instigating character education initiatives, and fostering collaborative partnerships. Following the principles of adjacent and incremental innovation, the institution consistently enhances teaching quality, facilities, and curriculum to meet evolving societal needs. Despite limitations, Islamic boarding schools steadfastly uphold their commitment to nurturing a generation that is intellectually adept, grounded in religious principles, and socially responsible. The research recommends continuous development of educational innovations within Islamic boarding school institutions and suggests future research to explore additional dimensions of their adaptation strategies during the modernization era. This will contribute to a more comprehensive understanding of the dynamic processes at play in Islamic boarding schools.